Autoconceitos de leitura erigidos a partir de narrativas de vida de professores alfabetizadores - Andrade, Francisco Rogiellyson da Silva (2019)
This Master’s Dissertation had as main objective to analyze self - concepts of reading erected from life stories narratives of literacy teachers. For this, we mobilize, from the theoretical presuppositions that emphasize us, three conceptions of reading: 1 - reducing, those that disregard the compression and / or confrontation of ideas and discourses as activities intrinsic to the act of reading; 2 - experience of life, which, through an introspective posture, the subject, through reading, can transform; and 3 - social practice, which allows the understanding of reading as an activity that takes place in specific social spheres and, as a result, that identity, discursive, ideological and cultural aspects intertwine in the interaction mediated by writing. Methodologically, we use the ethnossociological perspective elaborated by Bertaux (2010). This perspective, which falls within the scope of the case studies, understands that it is necessary to start from the subjects so that, subjectively, they interpret the social phenomena in which they are inserted. Thus, life narratives are the potential materials by which subjects narrate their experiences with a given object and reflect on it. In light of this, we collected oral narratives of life stories, recorded through voice recording applications, from the clinical perspective of collection, as reflected by Maia-Vasconcelos (2005), who understands the need for the researcher to bow before the subject, in order to give voice to him and, with that, to allow the interviewee to reflect on what he says, rather than wanting him to prove knowledge pre-formulated by the researcher. In light of this methodological construct, we interviewed eight literacy teachers. For analysis, which was also based on the clinical perspective elaborated by Maia-Vasconcelos (2005), three main categories of analysis were constructed for each specific objective: narratives that construct reading-reducing conceptions, narratives that construct reading as life experience and narratives who construct reading as social practice. The analysis allows the interpretation that the narrated experiences influence the pedagogical praxis of the subjects, who use different conceptions of reading to literate the students for which they are responsible. Thus, the self-concept constructed by the narratives are limited to the three approaches to reading constructed as categories of analysis. In addition, the subjects narrate that the schooling of literacy, therefore of reading, makes them perceive the act of reading in the light of conceptions that see the reading practice from moorings that measure the interpretation, considering there that the system itself privileges the oralization and the superficial analysis of the circulating texts in social practices.